2004
DOI: 10.1001/archneur.61.7.1108
|View full text |Cite
|
Sign up to set email alerts
|

A New Rare Mutation (691delCC/insAAA) in Exon 17 of the PYGM Gene Causing McArdle Disease

Abstract: To investigate the genetic effect of a new mutation found in exon 17 of the myophosphorylase (PYGM) gene as a cause of McArdle disease (also known as type 5 glycogenosis). Patients: A Spanish patient with McArdle disease was screened for 3 common mutations in the PYGM gene (R49X, W797R, and G204S), as previously described. The patient was heterozygous for R49X. To find other mutations, the coding sequence of the entire PYGM gene was sequenced. The carrier status of his relatives was also studied. Results: A no… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
4
0

Year Published

2005
2005
2015
2015

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(4 citation statements)
references
References 23 publications
0
4
0
Order By: Relevance
“…The latter has been shown to blunt cAMP activation of glycogen phosphorylase in skeletal muscle (20), in addition to having direct cardiac effects. The marked impairment of exercise capacity in McArdle's disease (21-23), due to heterogeneous nonsense mutations in the PYGM gene (24), also supports the contention that impaired carbohydrate flux can limit skeletal muscle function.…”
mentioning
confidence: 74%
“…The latter has been shown to blunt cAMP activation of glycogen phosphorylase in skeletal muscle (20), in addition to having direct cardiac effects. The marked impairment of exercise capacity in McArdle's disease (21-23), due to heterogeneous nonsense mutations in the PYGM gene (24), also supports the contention that impaired carbohydrate flux can limit skeletal muscle function.…”
mentioning
confidence: 74%
“…Additionally, more than 40 rare mutations are known [4,9,11]. However, there is little information about the frequency and distribution of these less common mutations among different ethnic groups.…”
Section: Introductionmentioning
confidence: 99%
“…As far as December 2005, 46 different PYGM mutations, 21 residing in the N-terminal and 25 in the C-terminal of the gene, have been identified in GSD-V patients (Deschauer et a. 2001, Mancuso et al 2003, Quintans et al 2004, Isackson et al 2005, Paradas et al 2005) (see also the Human Gene Mutation Database http://www.hgmd.cf.ac.uk/), making the diagnosis more accurate by DNA testing. In addition, muscle RNA studies demonstrated that a silent mutation leads to a severe alteration in mRNA splicing .…”
Section: Introductionmentioning
confidence: 99%